COGNITIVE CONSTRUCTION AND SHARIA RESPONSE: THEORETICAL FRAMEWORK OF PARENTAL REJECTION IN STUNTING DIAGNOSIS PHENOMENON - Afthon Yazid; Amila Ahsani; Faqih Abdulloh (Familia: Jurnal Hukum Keluarga, 2025)
The prevalence of stunting in several regions of Indonesia, including Tulung District, Klaten, remains above the national target. One of the main obstacles in addressing this issue is the phenomenon of parental rejection of the stunting diagnosis given to their children. This study aimed to analyze in depth the factors underlying this rejection and to examine them through Peter L. Berger and Thomas Luckmann’s social construction theory and the Maqāṣid al-Syari’ah framework. Using a qualitative method with in-depth interviews and participant observation, the study involved 4 inclusion informants (parents of children aged 6–59 months who rejected or ever rejected the stunting diagnosis) and 8 triangulation informants, including village midwives, nutrition officers, posyandu cadres, village officials, and religious leaders. The findings reveal that parents’ rejection of the stunting diagnosis is constructed through a social process and reinterpreted according to everyday experience, cultural norms, and emotional meanings of parental success. In Berger’s framework, this rejection represents a cycle of externalization of personal experience, objectivation through shared community beliefs, and internalization as social reality that resists medical authority. From the Maqāṣid al-Syari’ah perspective, this behavior reflects a contradicsm from the principles of hifz al-nafs (protection of life), hifz al-‘aql (protection of reason), and hifz al-nasl (protection of offspring).